Mapping the geography of disease: A comparison of epidemiologists' and field-level experts' disease maps. (January 2021) - Enticott, G.; Ward, K.; Ashton, A.; Brunton, L.; Broughan, J.
Highlights: Epidemiological maps of animal disease are used to manage disease and influence farmer behaviour. The paper analyses similarities between expert and farmer knowledges of animal disease spread. Three participatory mapping exercise are used to compare understandings of vulnerability and endemicity. Farmers' understandings of disease stress the importance of forms of disease mobility. Findings challenge binary categorisations of animal disease expertise suggesting a more complex relationship.